Perspektif Islam tentang Pendidikan dan Pembelajaran Karakter di SDN Pekayon 03 Pagi - rahmaini, nurul; Heni Ani Nuraeni; Mariani Claura Sihaloho (Mu'allim, 2025)
SDN Pekayon 03 Pagi, East Jakarta is a school that implements character education from an Islamic perspective for its students, as evidenced by students developing noble character in accordance with the teachings of the Qur'an and Sunnah. This research aims to analyze how Islamic character values are integrated into the educational process and their impact on students' character development. Using a descriptive qualitative method, data was collected through interviews, observations, and documentation. The findings show that Islamic values such as honesty, discipline, responsibility, and social care are instilled through three main strategies: daily habituation activities (including congregational prayers, morning prayers, and Clean Friday programs), teacher role modeling, and moral advice delivery. Religious programs like congregational Dhuha prayers, routine lectures, and social activities have proven effective in enhancing students' character development. While teachers serve as significant role models influencing student behavior, several challenges were identified, including limited instructional time, varying religious backgrounds among students, and insufficient parental support in implementing these values at home. The study concludes that systematically implemented Islamic character education produces students who excel both academically and in moral character development. The research emphasizes the importance of collaboration between schools and families in strengthening Islamic character values and suggests this model could serve as a reference for other educational institutions.